Regulation of Antibiotic Production by Signaling Molecules in Streptomyces - Kong, Dekun; Wang, Xia; Nie, Ju; Niu, Guoqing (Frontiers in Microbiology, 2019)
The genus Streptomyces is a unique subgroup of actinomycetes bacteria that are well-known as prolific producers of antibiotics and many other bioactive secondary metabolites. Various environmental and physiological signals affect the onset and level of production of each antibiotic. Here we highlight recent findings on the regulation of antibiotic biosynthesis in Streptomyces by signaling molecules, with special focus on autoregulators such as hormone-like signaling molecules and antibiotics themselves. Hormone-like signaling molecules are a group of small diffusible signaling molecules that interact with specific receptor proteins to initiate complex regulatory cascades of antibiotic biosynthesis. Antibiotics and their biosynthetic intermediates can also serve as autoregulators to fine-tune their own biosynthesis or cross-regulators of disparate biosynthetic pathways. Advances in understanding of signaling molecules-mediated regulation of antibiotic production in Streptomyces may aid the discovery of new signaling molecules and their use in eliciting silent antibiotic biosynthetic pathways in a wide range of actinomycetes.